Plant community establishment on the volcanic deposits following the 2006 nuées ardentes (pyroclastic flows) of Mount Merapi: Diversity and floristic variation - SUTOMO SUTOMO; RICHARD HOBBS; VIKI CRAMER (Society for Indonesian Biodiversity, 2011)
Sutomo, Hobbs R, Cramer V (2011) Plant community establishment on the volcanic deposits following the 2006 nuées ardentes (pyroclastic flows) of Mount Merapi: diversity and floristic variation. Biodiversitas 12: 86-91. Species establishment and composition changes in a substrate with little or no biological legacy is known as primary succession, and volcanoes, erosion, landslides, floodplains and glaciers are some type of disturbances that can create this kind of environment. Mount Merapi with its Merapi-type nuées ardentesor pyroclastic flows provides excellent opportunities to study primary succession. Using chronosequence approach, plant establishment and succession was studied, and thus five areas that were affected by nuées ardentes deposits between 1994 and 2006 were chosen as study sites. Results showed that there was a rapid colonization by vascular plants in primary succession as the sites aged. Imperata cylindrica, Eupatorium riparium, Anaphalis javanica, Athyrium macrocarpum, Brachiaria paspaloides, Dichantium caricosum, Selaginella doederleinii, Eleusine indica, Cyperus flavidus, Calliandra callothyrsus and Acacia decurrens were the species mainly responsible in explaining the differences between sites. Furthermore, the species richness and diversity reach their peak 14 years afterdisturbance.